Antioxidant and anti-inflammatory effects of polyphenols extracted from Ilex latifolia Thunb. Issue 13 (14th February 2018) - Zhang, Tian-Tian; Hu, Ting; Jiang, Jian-Guo; Zhao, Jing-Wen; Zhu, Wei
Abstract : To promote the application of Ilex latifolia Thunb., a Chinese bitter tea, polyphenols were extracted from its leaves and their cellular antioxidant activity (CAA) and anti-inflammatory effect against mouse macrophage RAW 264.7 cells were analyzed. Abstract : To promote the rational and effective application of Ilex latifolia Thunb., a Chinese bitter tea widely consumed as a health beverage, polyphenols were extracted from its leaves and their cellular antioxidant activity (CAA) and anti-inflammatory effect against mouse macrophage RAW 264.7 cells were analyzed. Results showed that the antioxidant capacity of polyphenols was high, and their CAA values in PBS wash and no PBS wash protocols were 6871.42 ± 85.56 and 25161.61 ± 583.55 μmol QE (quercetin equivalents)/100 g phenolic extracts, respectively. In addition, polyphenols from I. latifolia displayed strong inhibition on LPS-induced NO-production in RAW 264.7 cells. Polyphenol treatment inhibited the release of pro-inflammatory cytokines (TNF-α, IL-1β and IL-6) induced by LPS in a dose-dependent manner by ELISA and mRNA expression analysis. Western blot results showed that the anti-inflammatory activity of polyphenols from I. latifolia might be exerted through inhibiting the activation of MAPKs (ERK and JNK) and NF-κB to decrease NO, COX-2 and pro-inflammatory cytokines production. Thus, the polyphenol enriched extracts from I. latifolia are a good source of natural antioxidants with a beneficial effect against inflammation, and they may be applied as a food supplement and/or functional ingredient.